Metrological characteristics of an on-machine tool optical measuring system - Bissacco, Guiliano; Liltorp, Klaus; Nedrehagen, Ivan; Svinning, Øystein; Nielsen, Nicolaj Elias; Kruse, Christian Wissing; Shaheen, Amrozia (Cranfield University, 2022)
Metrological characterisation is a fundamental step towards assuring the traceability of a measuring instrument; particularly challenging for non-contact optical imaging systems due to the inadequacy of a specific reference standard for establishing the accuracy and traceability of the optical systems. In this paper, we have determined the metrological characteristics of an optical system for on-machine milling tool measurement. The evaluation procedure is in reliance with ISO 15530 part 3. An artefact was manufactured by wire electrical discharge machining method from a traceable cylindrical gauge pin into a square end. The artefact was measured using a coordinate measuring machine, and the task-specific measurement uncertainty is determined. The artefact was then utilised to characterise the optical measuring system in actual operating conditions, on-machine in a production workshop environment. Experiments have shown the applicability of the procedure and the suitability of the proposed calibration artefact for characterisation of tool diameter and run out.
TESConf_2022_paper_5683
11th International Conference on Through-life Engineering Services - TESConf 2022, 8-9 November 2022, Cranfield UK
Keywords: Coordinate metrology; uncertainty; optical system; calibration artefact; machine tool